Developing digital platforms’ actor value proposition for seller participants - Klinga, Matti (My University, 2025)
In the last decades, digital platform businesses have become an essential part of the world economy. Many of the world ́s largest companies are benefiting from platform business models, and their effect on people ́s everyday lives has increased significantly. Consequently, theoretical re- search on digital platforms has increased substantially during the last decades. Digital platform businesses and their value offerings have been studied from various angles, but there is a gap in the research in the understanding of how participants perceive the value that they are receiving for participating on the platforms. By understanding the needs of the participants better, it is possible to develop better digital platform businesses. This thesis focuses on the value perceptions of the seller-side participants on B2C platforms, where sellers are SME retailers and service providers. More specifically, the research is conducted on restaurants participating in food delivery platforms. The basis for the research is the actor value proposition, which has been developed as a framework regarding the value offering of digital platforms for the participants. Because of the fundamental differences in the value offering of platform business and traditional pipeline business, the concept of value proposition does not work similarly with platform businesses, and the actor value proposition has been developed in response to that. In this thesis, it is studied how the restaurants perceive the value that they are receiving for participating in the food delivery platforms. The results of the study are embedded in the actor value proposition and are used for the development of the original actor value proposition. As a result of the study, a revised actor value proposition for seller participants on digital platforms, where sellers are SME retailers and service providers, is presented. The revised actor value proposition can be used to develop better digital platform businesses, which better answer the needs of the platform seller-side participants.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development